Japanese Language Learning For Front Office Based On Role Playing In Diploma III Hospitality Program At Denpasar Academy Of Tourism - Ni Putu Sri Utami Putri; Eka Anastasia Wijaya (Denpasar Institute, 2023)
Japanese language learning is needed to help in preparing hospitality students to face the work field in line with the fact that the visit of Japanese tourists to Bali ranked in the top five. This study was done to examine the use of Japanese for hospitality especially front office through role-playing among the fifth-semester students of Diploma III Hospitality at Denpasar Academy of Tourism. This study was done in the form of qualitative research with observation as the research method. The result showed that the Japanese language learning done using role-playing method could maximize the practice of the students’ Japanese language as staff and guests with the given scenarios. Moreover, the use of role-playing helps the students to gain new knowledge through direct experience. It is also found that there were several challenges during the teaching and learning process such as the lack of appropriate gestures, mispronunciation, and time management. This study indicated that Japanese language learning is necessary in hospitality teaching and learning process to help the students to face the work field. It also implies that the lecturer especially Japanese lecturer need to highlight the use of role-playing during the teaching and learning process